Lethal combat over limited resources: testing the importance of competitors and kin. - Innocent, T; West, SA; Sanderson, J; Hyrkkanen, N; Reece, SE (2011)
Although most animals employ strategies to avoid costly escalation of conflict, the limitation of critical resources may lead to extreme contests and fatal fighting. Evolutionary theories predict that the occurrence and intensity of fights can be explained by resource value and the density and relatedness of competitors. However, the interaction between these factors and their relative importance often remains unclear; moreover, few systems allow all variables to be experimentally investigated, making tests of these theoretical predictions rare. Here, we use the parasitoid wasp Melittobia to test the importance of all these factors. In contrast to predictions, variation in contested resource value (female mates) and the relatedness of competitors do not influence levels of aggression. However, as predicted, fight intensity increased with competitor density and was not influenced by the greater cost of fighting at high density. Our results suggest that in the absence of kin recognition, indirectly altruistic behavior (spite) is unlikely to evolve, and in such circumstances, the scale of competition will strongly influence the amount of kin discrimination in the form of level of aggression as observed in Melittobia species.